Penerapan Elektronik Customer Relationship Management (E-CRM) Dalam Penjualan Roti Berbasis Web - Anggi Mela Ariska; Novica Irawati; Ahmad Muhazir (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
UD Roti Ali is a home industry engaged in the production of bread making. The rapid development of technology in the world has had a major influence on the performance of bread making in all business fields, especially in the food manufacturing business. The business strategy of retaining old customers is more profitable than finding new customers, so it is necessary to maintain relationships with customers. UD Roti ali does not yet have a strategy to get new customers to find out information about products and prices. Currently UD Roti Ali does not yet have the right relationship with customers, one of which is the sales and ordering process is still done manually, where customers directly come to UD Roti Ali or call to place an order for products, then recording customer order data is still done by recording in the memorandum, so errors often occur in recording customer order data. This affects the bakery business, so UD Roti Ali needs an electronic system using the CRM method to build and manage the right relationship between UD Roti Ali and its customers. Therefore, UD Roti Ali needs a special strategy regarding proper customer service and product marketing in electronic form using a web-based CRM (E-CRM) method which is useful for making it easier for UD Roti Ali and customers, for UD Roti Ali it is easier to manage sales data and customer data, while for customers it is easier for customers to find out information about products, make it easier to make orders, payments, as well as the discount/promo and bonus features provided by UD Roti Ali to customers. So that this web-based system can help UD Roti Ali in maintaining customer loyalty.